Penggunaan nada, intonasi, dan tekanan sebagai penguat makna dalam ceramah “the day of separation” oleh syeikh muhammad al-‘arifi - Putri, Fanny Aliyah (Maliki Interdisciplinary Journal, 2026)
The use of pitch and intonation in sermons is a paralinguistic component that plays an important role in strengthening meaning and enhancing the effectiveness of message delivery. As a form of oral communication aimed at providing understanding, motivation, and persuasion, sermons require delivery strategies that rely not only on the accuracy of content but also on the appropriateness of how the message is presented. Pitch and intonation help speakers emphasize certain parts of the material, signal topic transitions, and build an emotional atmosphere that aligns with the purpose of the sermon. Through the adjustment of pitch, tempo, and vocal stress, listeners can more easily grasp the main ideas, feel the urgency of the message, and maintain focus throughout the sermon. In addition, variations, in intonation can reduce monotony and increase audience engagement, making the delivered message more persuasive and meaningful. This article discusses the function of pitch and intonation as meaning enhancers in sermons, the factors influencing their use, and their impact on communication effectiveness. This study is expected to provide insight into the importance of vocal competence for speakers and encourage the application of more professional and communicative delivery techniques in sermon practices across various contexts.